2011
DOI: 10.1016/j.virol.2011.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Use of a tandem affinity purification assay to detect interactions between West Nile and dengue viral proteins and proteins of the mosquito vector

Abstract: West Nile and dengue viruses are (re)emerging mosquito-borne flaviviruses that cause significant morbidity and mortality in man. The identification of mosquito proteins that associate with flaviviruses may provide novel targets to inhibit infection of the vector or block transmission to humans. Here, a tandem affinity purification (TAP) assay was used to identify 18 mosquito proteins that interact with dengue and West Nile capsid, envelope, NS2A or NS2B proteins. We further analyzed the interaction of mosquito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 53 publications
1
38
0
Order By: Relevance
“…Accordingly, mutation of the basic residues might prevent interaction partners from entering the complex necessary for particle formation without affecting the NS2A-NS3 interaction itself or might interfere with RNA binding. For NS2A of DENV and WNV, several host proteins of mosquito origin, like translation factors or proteins involved in the cytoskeleton and cellular trafficking, have been found as binding partners (35). Further studies are necessary to determine whether these and analogous vertebrate proteins are involved in the formation of a complex necessary for assembly and release of infectious flavivirus particles.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, mutation of the basic residues might prevent interaction partners from entering the complex necessary for particle formation without affecting the NS2A-NS3 interaction itself or might interfere with RNA binding. For NS2A of DENV and WNV, several host proteins of mosquito origin, like translation factors or proteins involved in the cytoskeleton and cellular trafficking, have been found as binding partners (35). Further studies are necessary to determine whether these and analogous vertebrate proteins are involved in the formation of a complex necessary for assembly and release of infectious flavivirus particles.…”
Section: Discussionmentioning
confidence: 99%
“…To date, very few studies have been conducted to determine the interactome between DENV proteins and mosquito cellular proteins using sensitive and reliable protein interaction assays [22,23], with some predictions reported through a computational approach [24]. Hence, the aim of this study was to identify adult A. aegypti mosquito midgut proteins interacting with DENV-2 viral proteins, using an improved yeast twohybrid (Y2H) screening system, a high-throughput screening assay that allows identification of genuine protein interacting partners in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Involvement of host-factors in this particular region of the WNV RdRp could explain the host-dependent effects seen in this study. Thus far studies have shown the recruitment of host proteases in both the insect and vertebrate are required for viral polyprotein processing and a recent study demonstrated at least 18 mosquito proteins can interact with the WNV and DENV envelope, capsid, NS2a, and NS4b viral proteins in mosquito cell culture (Colpitts, Cox et al, 2011). However, little is known about host-factors that may interact with the viral replicase complex.…”
Section: Discussionmentioning
confidence: 99%